Diagnostic performance of ultrasound S-Detect technology in evaluating BI-RADS-4 breast nodules ≤ 20 mm and > 20 mm - Boyuan Xing; Chen Gu; Chenghui Fu; Bingyi Zhang; Yandi Tan (BMC Cancer)
Abstract Background This study aimed to explore the diagnostic performance of ultrasound S-Detect in differentiating Breast Imaging-Reporting and Data System (BI-RADS) 4 breast nodules ≤ 20 mm and > 20 mm. Methods Between November 2020 and November 2022, a total of 382 breast nodules in 312 patients were classified as BI-RADS-4 by conventional ultrasound. Using pathology results as the gold standard, we applied receiver operator characteristics (ROC), sensitivity (SE), specificity (SP), accuracy (ACC), positive predictive value (PPV), and negative predictive value (NPV) to analyze the diagnostic value of BI-RADS, S-Detect, and the two techniques in combination (Co-Detect) in the diagnosis of BI-RADS 4 breast nodules ≤ 20 mm and > 20 mm. Results There were 382 BI-RADS-4 nodules, of which 151 were pathologically confirmed as malignant, and 231 as benign. In lesions ≤ 20 mm, the SE, SP, ACC, PPV, NPV, and area under the curve (AUC) of the BI-RADS group were 77.27%, 89.73%, 85.71%, 78.16%, 89.24%, 0.835, respectively. SE, SP, ACC, PPV, NPV, and AUC of the S-Detect group were 92.05%, 78.92%, 83.15%, 67.50%, 95.43%, 0.855, respectively. SE, SP, ACC, PPV, NPV, and AUC of the Co-Detect group were 89.77%, 93.51%, 92.31%, 86.81%, 95.05%, 0.916, respectively. The differences of SE, ACC, NPV, and AUC between the BI-RADS group and the Co-Detect group were statistically significant (P < 0.05). In lesions > 20 mm, SE, SP, ACC, PPV, NPV, and AUC of the BI-RADS group were 88.99%, 89.13%, 88.99%, 91.80%, 85.42%, 0.890, respectively. SE, SP, ACC, PPV, NPV, and AUC of the S-Detect group were 98.41%, 69.57%, 86.24%, 81.58%, 96.97%, 0.840, respectively. SE, SP, ACC, PPV, NPV, and AUC of the Co-Detect group were 98.41%, 91.30%, 95.41%, 93.94%, 97.67%, 0.949, respectively. A total of 166 BI-RADS 4 A nodules were downgraded to category 3 by Co-Detect, with 160 (96.4%) confirmed as benign and 6 (all ≤ 20 mm) as false negatives. Conversely, 25 nodules were upgraded to 4B, of which 19 (76.0%) were malignant. The difference in AUC between the BI-RADS group and the Co-Detect group was statistically significant (P < 0.05). Conclusions S-Detect combined with BI-RADS is effective in the differential diagnosis of BI-RADS 4 breast nodules ≤ 20 mm and > 20 mm. However, its performance is particularly pronounced in lesions ≤ 20 mm, where it contributes to a significant reduction in unnecessary biopsies.